Quantifying Recording Quality in In Vivo Striatal Recordings. Issue 1 (5th January 2015) - Friend, Danielle M.; Kemere, Caleb; Kravitz, Alexxai V.
Abstract: The striatum mediates a variety of functions including movement, decision‐making, motivation, and reward learning. In vivo recording is a powerful technique that allows for the interrogation of these striatal functions while an animal is awake and behaving. Here, we describe equipment needed and general setup for performing in vivo electrophysiology experiments, data processing, and quantification of recording quality. While this protocol is focused on striatal recordings, concepts should translate to other structures as well. © 2015 by John Wiley & Sons, Inc.